2017
DOI: 10.5933/jkapd.2017.44.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ectopic Eruption of the Maxillary First Permanent Molar and Skeletal Malocclusion

Abstract: This study assessed the association between ectopic eruption of the maxillary first permanent molar and skeletal malocclusion in 5-to 10-year-old children. As subjects, 786 children who attended the Wonkwang University Dental Hospital for orthodontic diagnosis were included. Children with unerupted first permanent molars or fully erupted second permanent molars were excluded. The study group demonstrated ectopic eruption of the maxillary first permanent molar, while the control group did not. Cephalometric rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Bjerklin, in agreement with Pulver, found that there is a tendency for the length of the maxilla to be decreased [12]. Rah et al, in agreement with previous authors, concluded that poor jaw growth has an impact on EEM [16,20].…”
Section: Author Yearsupporting
confidence: 66%
See 1 more Smart Citation
“…Bjerklin, in agreement with Pulver, found that there is a tendency for the length of the maxilla to be decreased [12]. Rah et al, in agreement with previous authors, concluded that poor jaw growth has an impact on EEM [16,20].…”
Section: Author Yearsupporting
confidence: 66%
“…Table 5. Ectopic eruption of the maxillary first permanent molar prevalence data [1,5,[7][8][9]11,16,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…5 The prevalence of ectopic eruption of FPMs was reported between 0.75% and 11.8%, depending on the population studied. [4][5][6][7][8][9][10][11] In the present study, a prevalence of 2% was found, consistent with the prevalence results of some studies in the literature. 7,[24][25][26][27] The differences in these rates have been attributed to many factors, such as different sample sizes, patient inclusion criteria, diagnostic methods, assessment criteria, geography, ethnicity, age of the population, caries status, and genetic factors.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence rate of ectopic eruption of FPMs ranges from 0.75% to 11.8% in the normal population. [4][5][6][7][8][9][10][11] The variations in these prevalence rates have been associated with several factors including sample size, geographic location, ethnic background, age distribution, caries status, and genetic factors. 6,11 Higher prevalence rates were reported in siblings and patients with cleft lips or palates.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoral view, the delay in the eruption of unilateral or bilateral maxillary FPM, and the eruption of distal tubercles of these teeth before mesial tubercles should suggest the EE of these teeth. 7 In general, FPM with EE are impacted below the distal roots of PSM. 8 If they are not treated in time, they may lead to premature root resorption of PSM, pulp obliteration, neuralgic pain, or premature exfoliation, which may lead to premature loss of primary teeth, reduced arch length, and delayed eruption of permanent teeth.…”
mentioning
confidence: 99%